2017
DOI: 10.1038/s41598-017-06628-8
|View full text |Cite
|
Sign up to set email alerts
|

The global burden of lower urinary tract symptoms suggestive of benign prostatic hyperplasia: A systematic review and meta-analysis

Abstract: Benign prostatic hyperplasia is a common non-malignant condition among older men, but the epidemiology is poorly characterised. We summarised and determined the global prevalence of benign prostatic hyperplasia. A systematic search on PubMed, EMBASE and CENTRAL was performed up until 31st July 2016. Studies that described the epidemiology of benign prostatic hyperplasia were included and cumulative plots of prevalence estimates were calculated. A total of 31 prevalence rate estimates from 25 countries were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
124
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 44 publications
1
124
1
6
Order By: Relevance
“…Of 100 (17.4%) patients who reported TEAEs leading to permanent discontinuation of Patients who had Vesomni added to their original monotherapy with an α-blocker or 5-ARI. 2 Patients who were switched to Vesomni from their original monotherapy with an α-blocker or 5-ARI. 3 Patients who had Vesomni added to their original treatment with an α-blocker and 5-ARI monotherapy.…”
Section: Safety Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 100 (17.4%) patients who reported TEAEs leading to permanent discontinuation of Patients who had Vesomni added to their original monotherapy with an α-blocker or 5-ARI. 2 Patients who were switched to Vesomni from their original monotherapy with an α-blocker or 5-ARI. 3 Patients who had Vesomni added to their original treatment with an α-blocker and 5-ARI monotherapy.…”
Section: Safety Resultsmentioning
confidence: 99%
“…1 The global prevalence of LUTS has been estimated to range from 14.8% among men aged 40 to 49 years to 38.4% among men aged ≥ 80 years. 2 Notably, nearly half of the men with LUTS report both storage and voiding symptoms. 3 Although the underlying pathophysiology of LUTS has not been fully elucidated, changes in both prostate and bladder physiology have been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The combined prevalence of BPH is approximately 26.2% at the world level. 4 It is also reported that BPH increases with age and affect more than 70% of elderly males. 5,6 In order to reduce the complexities of BPH, innovative treatments developed in clinical practice have been widely employed with various efficacy and safety profiles.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis on studies from 25 countries showed that the lifetime prevalence of BPH was 26.2% [95% confidence interval (CI): 22.8-29.6%] and there were no regional or ethnic differences (Lee et al, 2017). In addition, in the United States alone, the annual spending on BPH treatment is estimated to be approximately $4 billion (Taub and Wei, 2006).…”
Section: Introductionmentioning
confidence: 99%